Early‐onset acral basal cell carcinomas in Gorlin syndrome. (1st October 2014) - Torrelo, A.; Vicente, A.; Navarro, L.; Planaguma, M.; Bueno, E.; González‐Sarmiento, R.; Hernández‐Martín, A.; Noguera‐Morel, L.; Requena, L.; Colmenero, I.; Parareda, A.; González‐Enseñat, M.A.; et al.
Summary: Two patients are reported in whom early‐onset, distal papules with a histopathological diagnosis of basal cell carcinoma were the first manifestation of Gorlin syndrome (GS). These lesions showed no progression and remained stable through follow‐up. Two different PTCH1 gene mutations were detected in the two patients, and thus a phenotype–genotype correlation of this manifestation of GS was not possible. Abstract : What's already known about this topic? Gorlin syndrome (GS) shows a variety of basaloid hamartomatous lesions and basal cell carcinomas (BCCs). What does this study add? Acral BCCs appearing at birth or in infancy may be the initial manifestation of GS. Acral BCCs are an unusual manifestation of GS.